A "reinvenção" da favela urbanização de favelas na era do marketing urbano: o caso do Rio de Janeiro - Francielle Evelyn Mendes Gomes (2014)
The crisis of Fordism, in the second half of the twentieth century, boosted the current phase of financial capitalism based on the dissemination of the idea of globalization, supported by scientific and technological advances, and the strengthening of the neoliberal paradigm. These transformations generate impacts in urban planning system of large cities, making emerge the new strategic planning model supported the global competition between cities for investment and resources by consolidating a strong and attractive image. This contemporary capitalism, when faced with cultural elements as potential authentic and special products related to a particular place, creates forms of monopoly rent as strategic possibilities explored by the new planning model. The city of Rio de Janeiro, to become competitive, investing in strengthening a distinct identity. The Rio slums have always been part of an imaginary, before related to dirty, ugly, poor and therefore undesirable. Today they are accepted as part of patrimony of Rio and are represented as ghetto of their own culture and therefore valued, in addition to contain urban poverty, drug traffic and violence, recurrent elements in the conception of a Third World scenario. Therefore, the Rio slums are authentic and original. So, they are commodities. The objective of this work is to analyze the role of large urban mobility equipment installed in three Rio slums in the consolidation of an alternative and suitable tourism market for the transformation of the slums at cultural element and the conception of a global robust image of the city of Rio de Janeiro.